2016
DOI: 10.1142/s0219455415500194
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Flutter and Nonlinear Dynamics of a Composite Laminated Plate

Abstract: This paper presents the analysis of°utter and nonlinear dynamics of an orthotropic composite laminated rectangular plate subjected to aerodynamic pressures and transverse excitation. Thē rst-order linear piston theory is employed to model the air pressures. Based on Reddy's thirdorder shear deformation plate theory and von Karman-type equation for the geometric nonlinearity, the nonlinear governing equations of motion are derived for the composite laminated rectangular plate by applying the Hamilton's principl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The system becomes unstable if the real part of the eigenvalues r is positive. [31][32][33][34] For a perfectly tuned slender structure, all uncoupled structural natural frequencies and damping ratios for transverse and rotational vibrations are set equal to each other, in which ! yk ¼ !…”
Section: Analytical Solutionmentioning
confidence: 99%
“…The system becomes unstable if the real part of the eigenvalues r is positive. [31][32][33][34] For a perfectly tuned slender structure, all uncoupled structural natural frequencies and damping ratios for transverse and rotational vibrations are set equal to each other, in which ! yk ¼ !…”
Section: Analytical Solutionmentioning
confidence: 99%
“…Several types of damping treatments have been estimated and the results indicated that damping properties had important influences on the flutter boundaries of these sturctures. Chen et al [4,5] investigated the nonlinear response and aeroelastic flutter of composite laminated plates and shells under the combined excitation of aerodynamic pressures and transverse excitation. Yang et al [6] studied the supersonic flutter of laminated composite plate concluding a viscoelastic mid-layer and examined the influences of viscoelastic damping and aerodynamic damping on the flutter boundary of the plate.…”
Section: Introductionmentioning
confidence: 99%